Uliana Hrab, „Myroslaw Antonowycz: Intelektual’na biografiya. Emihraciine muzykoznavstvo v ukraiins’komu kul’turotvorenni povoyennykh desyatylit’ ”, Lviv 2019 - Berehova, Olena (Muzyka, 2022)
Recenzja książki: Uliana Hrab, Myroslaw Antonowycz: Intelektual’na biografiya. Emihraciine muzykoznavstvo v ukraiins’komu kul’turotvorenni povoyennykh desyatylit’ [Myroslaw Antonowycz: Intellectual biography. Emigrational musicology in the Ukrainian culture formation of the post-war decades], Lviv 2019